Carbon coated nickel–cobalt bimetallic sulfides hollow dodecahedrons for a supercapacitor with enhanced electrochemical performance. (7th March 2018) - Huang, Teng; Song, Xue-Zhi; Chen, Xi; Chen, Xiao-Lei; Sun, Fei-Fei; Su, Qiao-Feng; Li, Ling-Dong; Tan, Zhenquan
Abstract : Bimetallic sulfides coated by carbon hollow dodecahedrons were synthesized from bimetallic ZIFs as precursors and exhibited enhanced electrochemical performance as supercapacitors. Abstract : Due to the high power density and long cycle life, supercapacitors have been regarded as one of the most promising energy storage devices. In the present work, by the sulfuration of Ni–Co coexisting well-defined ZIF-67 dodecahedrons, hollow bimetal sulfides composed of Ni3 x Co3−3 x S4 nanobuilding blocks were successfully achieved. Subsequently, after hydrothermal treatment by glucose, the bimetallic sulfides were coated by carbon, leading to the formation of Ni3 x Co3−3 x S4 @carbon (NCSC- x, x = 0.2) hollow dodecahedrons. When evaluated as a supercapacitor electrode, the specific capacitance of NCSC-0.2 can reach 696 F g −1 and 480 F g −1 in KOH (6 M) at the current densities of 1 A g −1 and 20 A g −1, respectively, which are much higher than those (305 F g −1 and 116.7 F g −1 ) of bare Ni3 x Co3−3 x S4 (NCS-0.2, x = 0.2) under the same measurement conditions. Furthermore, the NCSC-0.2 electrode presents a better cyclic stability, with 73% capacitance retention after 2000 charge and discharge cycles at a current density of 10 A g −1 . The synergistic effect of the bimetallic components, hollow structures and carbon coating accounts for the enhanced electrochemical performance, paving the way towards other advanced supercapacitors for future high-performance energy storage by using structurally designed and suitably functionalized MOFs based nano-precursors.